2015
DOI: 10.1038/mt.2014.163
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 Modulates Angiogenesis In Vitro and in a Mouse Model of Limb Ischemia

Abstract: Epigenetic mechanisms may regulate the expression of pro-angiogenic genes, thus affecting reparative angiogenesis in ischemic limbs. The enhancer of zest homolog-2 (EZH2) induces thtrimethylation of lysine 27 on histone H3 (H3K27me3), which represses gene transcription. We explored (i) if EZH2 expression is regulated by hypoxia and ischemia; (ii) the impact of EZH2 on the expression of two pro-angiogenic genes: eNOS and BDNF; (iii) the functional effect of EZH2 inhibition on cultured endothelial cells (ECs); (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 50 publications
3
51
1
1
Order By: Relevance
“…Consistent with these results, Smits et al showed that decreased expression of miR-101, a repressor of EZH2 expression, in ECs results in increased blood vessel formation [142]. Consistent with these data, EZH2 was found to be bound to eNOS and BDNF promoters where it mediates H3K27 tri-methylation in normoxia and hypoxia [144]. capillary-like structure formation) it also increases other angiogenic properties such as adhesion and migration [143], suggesting that EZH2 inhibition could potentially be useful to improve the function of endothelial progenitors for stem cell therapy.…”
Section: H3k27 Methylation In the Endothelial Lineagementioning
confidence: 55%
See 3 more Smart Citations
“…Consistent with these results, Smits et al showed that decreased expression of miR-101, a repressor of EZH2 expression, in ECs results in increased blood vessel formation [142]. Consistent with these data, EZH2 was found to be bound to eNOS and BDNF promoters where it mediates H3K27 tri-methylation in normoxia and hypoxia [144]. capillary-like structure formation) it also increases other angiogenic properties such as adhesion and migration [143], suggesting that EZH2 inhibition could potentially be useful to improve the function of endothelial progenitors for stem cell therapy.…”
Section: H3k27 Methylation In the Endothelial Lineagementioning
confidence: 55%
“…In addition, EZH2 silencing in tumor-associated ECs decreases angiogenesis through VASH1 re-expression, leading to decreased cancer growth [141]. A very recent study [144] highlighted the role of EZH2 in ischemic vascular repair. Interestingly, while EZH2 silencing in ECs reduces some of the cells' angiogenic properties (e.g.…”
Section: H3k27 Methylation In the Endothelial Lineagementioning
confidence: 99%
See 2 more Smart Citations
“…30 We also showed that Ad-mediated EZH2-α overexpression impairs the angiogenic capacity of healthy HUVECs in vitro. 30 The results of our 2 studies can be reconciled if we speculate that hypoxia/ischemia and HG/GDM regulate different EZH2 isoforms and other RNAbinding molecules in ECs and that changes in EZH2-α and EZH2-β expression differently affect gene regulation.…”
Section: Discussionmentioning
confidence: 85%